A first screening of black carbon concentrations whilst commuting by diesel-fuelled buses in Montevideo, Uruguay - Admir Créso Targino; Camila Couto da Costa; Patricia Krecl (Heliyon)
Urban bus commuters are exposed to a range of traffic-related air pollutants, including black carbon (BC) particles, a major hazardous component of vehicle exhaust emissions. This study provides the first assessment of in-cabin BC concentrations aboard diesel-fuelled public buses in Montevideo, Uruguay. Our objective was to assess BC concentrations during evening peak commuting hours and to examine how specific traffic elements, such as bus stops, traffic lights and traffic volume, influence exposure levels. We implemented a structured sampling strategy to maximise the reliability of our findings by collecting data during four consecutive weekdays within the same timeframe (17:00–18:00 h) in May 2019. We measured BC concentrations at a high-frequency sampling rate using a handheld aethalometer, focusing on two bus routes. The mean in-cabin BC concentration was 14.28 ± 14.38 μg m⁻³, with considerable spatial variability. Notably, BC concentrations were significantly higher at traffic lights and bus stops, where stop-and-go driving patterns and idling contribute to increased emissions, while the constant opening and closing of doors allows outside air to infiltrate. We found a positive trend between traffic volume and median BC concentrations, consistent with previous studies conducted in other cities. Compared to similar studies in South America, BC concentrations were found to be intermediate, but considerably higher than those observed in North American and European cities. This study underscores the importance of implementing targeted interventions in urban transport policies, specifically addressing congestion points, like bus stops and traffic lights, to effectively reduce commuter exposure to harmful air pollutants. Whilst our study focused on Montevideo, interventions to combat traffic-related air pollutants should be expanded across Latin American cities, where reliance on diesel-powered public transportation remains prevalent.